2022
DOI: 10.1111/ajps.12692
|View full text |Cite
|
Sign up to set email alerts
|

How Terrorism Does (and Does Not) Affect Citizens’ Political Attitudes: A Meta‐Analysis

Abstract: How does terrorism affect citizens’ political attitudes? Over the years, many scholars have tried to answer this question. This article performs a meta‐analysis on this literature, reviewing about 325 studies conducted between 1985 and 2020 on more than 400,000 respondents. The findings confirm that terrorism is associated—to a small but significant extent—with outgroup hostility, political conservatism and rally‐‘round‐the‐flag effects. At the same time, the effects of terrorism vary widely, with studies on I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(78 citation statements)
references
References 89 publications
3
75
0
Order By: Relevance
“…The average magnitude of the effect of trust on all outcomes in the dataset is 0.08 (CI = [0.06, 0.10]). To put these effect sizes into context, other meta-analyses in political science have found that terrorism has an effect of 0.09 on rally effects to 0.132 for a conservative shift (measured in Fisher's Z, the same unit as here) (Godefroidt, 2021); that ethnic diversity has an effect of -0.025 on social trust (Dinesen et al, 2020); and that globalisation has an effect size of -0.1 on public spending (Heimberger, 2020). According to these results, the effect of trust is considerably larger than that of ethnic diversity on social trust and equivalent to, or slightly smaller than, the effect of terror attacks on a range of attitudinal outcomes.…”
Section: The Effect Of Trustmentioning
confidence: 92%
See 2 more Smart Citations
“…The average magnitude of the effect of trust on all outcomes in the dataset is 0.08 (CI = [0.06, 0.10]). To put these effect sizes into context, other meta-analyses in political science have found that terrorism has an effect of 0.09 on rally effects to 0.132 for a conservative shift (measured in Fisher's Z, the same unit as here) (Godefroidt, 2021); that ethnic diversity has an effect of -0.025 on social trust (Dinesen et al, 2020); and that globalisation has an effect size of -0.1 on public spending (Heimberger, 2020). According to these results, the effect of trust is considerably larger than that of ethnic diversity on social trust and equivalent to, or slightly smaller than, the effect of terror attacks on a range of attitudinal outcomes.…”
Section: The Effect Of Trustmentioning
confidence: 92%
“…2 Blair et al (2021) identified just five in five leading 3 political science journals between 1999 and 2018 (e.g Lau et al, 1999), and just one of these used observational research. The use of meta-analyses has been increasing, with recent studies focusing on topics such as social trust and ethnic diversity (Dinesen et al, 2020), terrorism and political attitudes (Godefroidt, 2021), natural resources and conflict (Blair et al, 2021;O'Brochta, 2019), effects of political incivility (Van 't Riet & Van Stekelenburg, 2021), and gender and candidate choice (Schwarz & Coppock, 2021). Despite this, they are relatively sparse, often do not use observational data, and employ different analytical strategies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we argue conspiracy theories and collective narcissism serve (both to politicians and their audiences) a common function to justify and perpetuate societal polarization and intergroup tensions between groups at different levels of social hierarchies and intergroup hostilities in the context of intergroup conflicts. They help create and perpetuate threatening environments where violence easily escalates and people rally around authoritarian leaders, preferring undemocratic to democratic governance [50] (at least in its representative and deliberative forms [51]).…”
Section: Collective Delusions That Render Violence a 'Logical Conclus...mentioning
confidence: 99%
“…For example,Yam et al (2020) find that the rise of COVID-19 cases is associated with support for political leaders, using individual data from 11 countries.28 An exception isGodefroidt (2022) who makes a clear distinction.…”
mentioning
confidence: 99%